Engineering Masculinities: How Higher Education Genders the Water Profession in Peru. Issue 2 (4th May 2017) - Rap, Edwin; Oré, Maria Teresa
ABSTRACT: By telling the story of an agricultural university in Peru, this article shows how a specific professional formation forges a strong linkage between engineering and masculine identities in water management. Although these identities come to be seen as self-evident or even natural, they are the outcome of diverse, repeated, and ritualized performances as part of the everyday life of the university. Through collectively enacting and experiencing such cultural performances, engineering students are trained to do science and technology in specific ways, ways that embody particularly masculine symbolic repertoires. On becoming part of a professional society, through rites of passage such as hazing and field work, students simultaneously learn to behave as engineers and become 'real' men. Building on and sometimes actively re-working existing societal markers of hierarchy and difference, male engineers in this process distinguish themselves from non-engineers, women and 'other' men. With careful interviewing and observation of agricultural engineers, the article suggests an interpretive framework to analyse the multiple cultural and performative repertoires that 'engineer' specific masculinities.